2011
DOI: 10.7150/ijbs.7.180
|View full text |Cite
|
Sign up to set email alerts
|

Novel and Conserved Micrornas in Dalian Purple Urchin (Strongylocentrotus Nudus) Identified by Next Generation Sequencing

Abstract: MicroRNAs are regulators in regulation of broad range of phenotypes. The purple urchin, Strongylocentrotus nudus, is one of the most important marine economic animals that widely distributed in the cold seas along the coasts of eastern pacific area. To date, only 45 microRNAs have been identified in a related species, Strongylocentrotus purpurtus, and there is no report on S. nudus microRNAs. Herein, solexa sequencing technology was used to high throughput sequencing analysis of microRNAs in small RNA library … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 48 publications
(73 reference statements)
6
39
0
Order By: Relevance
“…2). Overall, the distribution of sRNA size in this study was consistent with the results reported in other model plant species, such as Arabidopsis (Rajagopalan et al 2006) and rice (Wei et al 2011).…”
Section: Sequence Analysis Of Srnas In Radishsupporting
confidence: 92%
See 1 more Smart Citation
“…2). Overall, the distribution of sRNA size in this study was consistent with the results reported in other model plant species, such as Arabidopsis (Rajagopalan et al 2006) and rice (Wei et al 2011).…”
Section: Sequence Analysis Of Srnas In Radishsupporting
confidence: 92%
“…Then, transcriptome de novo assembly was carried out using the short-read assembling program Trinity (Grabherr et al 2011). A proprietary pipeline script, ACG T101-miR v4.2 (LC Sciences, Houston, TX, USA), was used for sRNA sequencing data analysis (Li et al 2010a;Wei et al 2011). The key functions of this script included removing various unmappable sequencing reads by a series of digital filters and performing mappable unique sequencing to the latest release of miRBase and the reference genome sequences.…”
Section: Bioinformatics Analysesmentioning
confidence: 99%
“…Sequencing data analysis was performed using the proprietary ACGT101-miR v4.2 pipeline script (LC Sciences; Li et al 2010, Meyer et al 2011, Wei et al 2011. After adapter trimming and quality Þltering of 28,574,374 raw reads, 22,543,231 (78.9%) of the reads were mapped to the following databases: Drosophila melanogaster Meigen genomic or transcript sequences (FlyBase assembly r5.44, ftp://ftp.ßybase.net/) and miRBase 18 (GrifÞths-Jones et al 2008, Kozomara and GrifÞths-Jones 2011; ftp://mirbase.org/), including both mature miRNAs (miRs) and premiRs for 28 arthropod species, including representative data from Diptera (dme, dan, der, dgr, dmo, dpe, dps, dse, dsi, dvi, dwi, dya, aae, aga, ame, cqu), Lepidoptera (bmo), Coleoptera (tca), Hemiptera (api), Hymenoptera (ngi, nlo, nvi), and Orthoptera (lmi), as well as noninsect mandibulate (smr, dpu) and chelicerate (isc, rmi) species.…”
Section: Rna Isolation and Small Rna Library Preparationmentioning
confidence: 99%
“…Previous microRNA profiling studies using microarrays or deep-sequencing have separated a small subset of highly expressed microRNAs from a larger group of microRNAs that are expressed at low levels (Shao et al, 2010;Cristino et al, 2011;Li et al, 2011;Wei et al, 2011). Based on these studies, we assigned a cutoff of 1000 intensity units above which microRNAs would be considered as highly expressed to generate a subset of microRNAs for closer comparison.…”
Section: General Findings On Microrna Expressionmentioning
confidence: 99%